Values of the angles of trunk rotation in two body positions - Beata Żuk; Katarzyna Tołłoczko; Monika Lewandowska; Maria Sobol (Medycyna Ogólna i Nauki o Zdrowiu, 2022)
Introduction and objective Early detection of trunk rotation abnormalities in schoolchildren should be a basis for the prevention of three-plane spinal deformities. Scoliometric evaluation enables reliable, reproducible selection of schoolchildren requiring extended orthopaedic diagnostics. The accepted SOSORT recommendations for the interpretation of trunk rotation angle values need to be popularized mainly in preventive health care teams. The aim of the study was to evaluate trunk rotation angles and total trunk rotation in schoolchildren aged 8–12 years in two body positions.